Characterization of the neural stem cell gene regulatory network identifies OLIG2 as a multifunctional regulator of self-renewal - Mateo, Juan L.; Ettwiller, Laurence; Wittbrodt, Joachim (Genome research, 2015)
An international, peer-reviewed genome sciences journal featuring outstanding original research that offers novel insights into the biology of all organisms
Gesehen am 07.02.2017